Partial Discharge Testing on MV Motor – Case Study - Siwakorn Jeenmuang; Warisanan Rojanasunan; Kritsada Dorkmai; Komin Chumpiboon; Patt Udomluksananon; Norasage Pattanadech (My University, 2023)
A failure of a medium voltage (MV) motor during its operation could force an outage of the power plant and also lead to a loss of cost. Hence, the method to ensure the insulation quality of such a motor is needed. Partial discharge (PD) testing is one of the effective methods used to determine the defect and evaluate the integrity of the machine insulation. This paper presents the application of off-line PD testing on MV motors. In the experiment, the PD test instrument conforming to standard IEC 60270 was used as a charge-based measurement. Moreover, during the PD testing, an acoustic imaging camera was employed as an alternative technique for locating the PD sources in the stator winding part. Once PD takes place, it can generate the pressure acoustic wave that propagates surrounding the PD source. Thus, the PD source in the area of endwinding can be located by this technique. From the charge-based PD test results, the phase-resolved PD (PRPD) pattern was considered to identify the type of PD source. It was found that almost MV motors tested have delamination in the bulk insulation. In some cases, the PRPD pattern exhibits the discharge in the area of the overlap region between the semiconductive and stress grading coating in the slot exit, which confirms by using the acoustic technique.
Keywords: High voltage insulation and dielectric phenomena; Thermal Analysis in Power Transmission; Non-Destructive Testing Techniques